The Relationship between the Role of Buddhist College Workers and Their Participation as Members of the Buddhi Employee Cooperative in Tangerang - Agus Kusnawan; Indra Gunawan; Eso Hernawan (Fakultas Bisnis, 2021)
The purpose of the research is to obtain the value of the relationship between the roles of female Buddhist college employees on participation as members of the Buddhist college employees employee cooperative in Tangerang. As for the background of this research is the enormous role of cooperatives, especially in Indonesia in advancing the family economy. In addition, the condition of women working in Indonesia is increasingly having a very helpful role for the family economy. The data in this study are the result data from questionnaires conducted by the research team. This research uses descriptive analysis method where the results of this study provide an overview of the phenomenon of the object of research. This study uses relationship analysis and t test and r test in data processing. The respondents who were studied from the age side, most were in the productive age between 20 - 45 years old or as much as 86.50%. Of the educational structure 73% of respondents have education with a bachelor to doctoral level. The calculation result of simple correlation (r) shows the correlation value of 0.326. This shows the correlation between the role of female employees with the role of members of the Buddhist college employees cooperative in Tangerang does not have a correlation even though the degree of relationship shown shows a positive number. Hypothesis testing in this study shows a significance value> 0.05 then Ho is accepted, meaning that no significant correlation is described between the role of female employees with the roles or functions of members of the Buddhist college employees cooperative in Tangerang. The conclusion from this study is that there is no relationship between the role of female college employees and their participation as members of the Buddhist employee cooperative in Tangerang.